2010
DOI: 10.1111/j.1540-8191.2009.00984.x
|View full text |Cite
|
Sign up to set email alerts
|

What's New in Cardiac Cell Therapy? Allogeneic Bone Marrow Stromal Cells as “Universal Donor Cells”

Abstract: Cardiac cell therapies offer distinct and exciting advantages over current treatments to prevent postinfarction heart failure because they can reverse ventricular remodeling and improve function, but only if the implanted stem cells contribute biological functions and achieve prolonged engraftment within the hostile environment of the damaged heart. Unfortunately, function is diminished in autologous stem cells isolated from older patients and those with comorbidities, and so clinical trials testing the implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 82 publications
0
25
0
Order By: Relevance
“…Together, our findings strongly support the ongoing development of allogeneic MSC therapy in patients with a variety of chronic conditions. 8,15,29,30,34 …”
Section: Commentmentioning
confidence: 99%
“…Together, our findings strongly support the ongoing development of allogeneic MSC therapy in patients with a variety of chronic conditions. 8,15,29,30,34 …”
Section: Commentmentioning
confidence: 99%
“…While some proponents believe advanced stem cell donor age results in diminished function (17-21), other studies raise a clinically relevant issue as to whether recipient age is a crucial factor limiting response to cell therapy (22-24). This has led to the notion that MSC therapy outcome depends not only on stem cell age, and thus function, but also recipient age and comorbidities (9,22).…”
Section: Introductionmentioning
confidence: 99%
“…This has led to the notion that MSC therapy outcome depends not only on stem cell age, and thus function, but also recipient age and comorbidities (9,22). Indeed, reduced responsiveness as a function of donor age would be a major limitation to the emerging development of cell therapy for heart disease, given the increasing incidence and morbidity of heart disease with age (25).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the Revascor trial is another randomized, placebo‐controlled multicenter trial that assesses the safety and feasibility of three different doses of allogeneic MSCs delivered into the myocardium of patients with chronic heart failure. After 3 months, their preliminary results were also reported online (http://www.angioblast.com) and described a significant improvement in the overall ventricular function [50]. More importantly, promising results of the phase II trial were recently reported at the 2011 meeting of the American Heart Association (held in Orlando, FL).…”
Section: Clinical Trials Involving the Allogeneic Use Of Mscsmentioning
confidence: 99%